Absorption, disposition and metabolic pathway of amiselimod (MT-1303) in healthy volunteers in a mass balance study. (2nd September 2019) - Kifuji, Takayuki; Inoue, Shinsuke; Furukawa, Megumi; Perez Madera, Begonya; Goto, Takahiro; Kumagai, Hiroshi; Mair, Stuart J; Kawaguchi, Atsuhiro
Abstract: The absorption, metabolism and excretion of MT-1303 were investigated in healthy male subjects after a single oral dose of 0.4 mg [14C]-MT-1303 (ClinicalTrials.gov NCT02293967). The MT-1303 concentration in the plasma reached a maximum at 12 h after administration. Thereafter, the concentration declined with a half-life of 451 h. At the final assessment on Day 57, 91.16% of the administered radioactivity was excreted, and the cumulative excretion in the urine and faeces was 35.32% and 55.84%, respectively. The most abundant metabolite in plasma was MT-1303-P, which accounted for 42.6% of the area under the plasma concentration–time curve (AUC) of the total radioactivity. The major component excreted in urine was Human Urine (HU)4 (3066434), accounting for 28.1% of radioactivity in the sample (4.05% of the dose), whereas MT-1303 was a major component in the faeces, accounting for 89.8% of radioactivity in the sample (25.49% of the dose) up to 240 h after administration. This study indicates that multiple metabolic pathways are involved in the elimination of MT-1303 from the human body and the excretion of MT-1303 and MT-1303-P via the kidney is low. Therefore, MT-1303 is unlikely to cause conspicuous drug interactions or alter pharmacokinetics in patients with renal impairment. Trial registration: ClinicalTrials.gov identifier: NCT02293967.